الموت الجماعي في المغرب الإسلامي - حداد, أحمد; ليبدري, بلخير (جامعة الوادي - University of Eloued, 2022)
الملخص: هذا البحث دراسة في أسباب الموت الجماعي من خلال عملية جرد وإحصاء للعديد من الأزمات السياسية والكوارث الطبيعية التي مست مغرب العصر الوسيط، تهدف إلي بيان تأثير هذه الأزمات في المجتمع المغربي، تمثلت في ثلاث أزمات كبيرة: مجاعات أوبئة وحروب، كانت مخلفاتها كارثية علي كل الجوانب وخاصة علي الجانب الديمغرافي، شكلت العلاقة التكاملية التي كانت تربط بين هذه الأزمات الثلاثة مشكلة عويصة أخري بحيث تَحدُث هذه الأزمات متوالية تسبقها المجاعات بنقص الأمطار وقلة المجابي، وتكتمل بحدوث الأوبئة والحروب، وهي التي أسهمت في تراجع رهيب في العنصر البشري إذ تحتاج فترات زمنية كبيرة لإعادة إعمار المنطقة، وبالرغم من عدم إعطاء المصادر لإحصائيات رسمية تعبر عن الخسائر بصفة دقيقة إلا اننا حاولنا الوصول لإحصائيات تقريبية عن هول الخسائر وعظمها من خلال العديد من القرائن. This research is a study of the causes of mass death through an inventory and census of many political crises and natural disasters that affected medieval Maghreb, aiming to show the impact of these crises on Maghrebian society, represented by three major crises: famines, epidemics and wars, the remnants of which were catastrophic on all sides Especially on the demographic side, the complementary relationship that connected these three crises constituted another severe problem, as these crises occur in sequence, preceded by famines, due to lack of rain and lack of response, and complete with the occurrence of epidemics and wars, which contributed to a terrible decline in the human element, as large periods of time need to be restored. Reconstruction of the area, and although the sources did not give official statistics that accurately express the losses, we tried to reach an approximation of the size and magnitude of the losses through many clues.
مقال
Keywords: المغرب الإسلامي، الموت، المجاعات، الوباء، الحروب; the Islamic Maghreb, death, famine, epidemic, wars